The Role and Responsibilities of Creditors in Handling Debtor Bankruptcy Cases: Ensuring Justice and Balance in The Legal Process - Mukianto, Jandi (International Journal of Sociology and Law, 2025)
Business entities often face bankruptcy risks due to various factors, including accounting errors, limited experience, or small-cap transactions. The COVID-19 pandemic exacerbated financial conditions for many companies, such as PT Garuda Indonesia (Persero) Tbk., which experienced a significant revenue decline. Additionally, individuals may face bankruptcy due to reasons like job termination or business failures. The primary cause of bankruptcy lies in the imbalance between debt and income, often worsened by poor financial planning. Government regulations can help mitigate bankruptcy risks, such as through health insurance and credit restrictions. The bankruptcy process aims to provide fair resolutions between debtors and creditors while safeguarding public interests. Bankruptcy can also offer debtors the opportunity to restructure their debt, maintain economic stability, and prevent social loss. In practice, bankruptcy involves the management of the debtor's assets by a trustee and the proportional distribution of proceeds to creditors. The application of freedom of contract and legal certainty principles in debtor-creditor relationships is crucial to ensuring a transparent, efficient, and equitable process.